2011
DOI: 10.1113/jphysiol.2011.210237
|View full text |Cite
|
Sign up to set email alerts
|

Robust L‐type calcium current expression following heterozygous knockout of the Cav1.2 gene in adult mouse heart

Abstract: Non-technical summary Appropriate regulation of ion channel expression is critical for the maintenance of both electrical stability and normal contractile function in the heart. A classic way to study the robustness of biological systems is to examine the effects of changes in gene dosage. We have studied how the heart responds to changes in the L-type calcium channel gene dosage. Homozygous Cav1.2 knockout in the adult heart is lethal, without compensatory responses in expression of other calcium channel gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 49 publications
3
23
0
Order By: Relevance
“…ND means not determined as the signal-to-noise ratio was too small in the absence of Ca V ␣2␦1. (10) tracked by the external HA epitope and the intracellular mCherry tag, respectively. The constitutive mCherry fluorescence was used as an index of Ca V ␣2␦ expression under all conditions for the wild-type protein as well as the Ca V ␣2␦ mutants (see below).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ND means not determined as the signal-to-noise ratio was too small in the absence of Ca V ␣2␦1. (10) tracked by the external HA epitope and the intracellular mCherry tag, respectively. The constitutive mCherry fluorescence was used as an index of Ca V ␣2␦ expression under all conditions for the wild-type protein as well as the Ca V ␣2␦ mutants (see below).…”
Section: Discussionmentioning
confidence: 99%
“…Its unique role is substantiated by the observation that homozygous knock-out of the CACNA1C gene is lethal (9,10). In addition to initiating the coordinated contraction of the cardiac ventricles, Ca V 1.2 channels are critical to the heart's normal rhythmic activity (8).…”
mentioning
confidence: 99%
“…Hence, it remains uncertain how these data relate to our observations in α1C -/+ and α1C fl/fl-Cre mice that did show reduced current, α1C protein, and cardiac function. Indeed, Rosati et al recently showed that heart-specific deletion of α1C resulted in reduced cardiac function and early postnatal lethality, although heterozygous deleted mice showed no baseline phenotype in their analysis (33). These disparities notwithstanding, perhaps the most important observations are from clinical trials with Ca 2+ channel antagonists, which failed to show protective effects in patients with heart failure with systolic dysfunction and, in some cases, showed signs of worsening disease and increased mortality (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Ca 21 flow through these channels serves as the second messenger of electrical signaling, initiating intracellular events such as contraction, secretion, synaptic transmission, fertilization, and gene expression [10]. Mice with the inducible knockout of Ca V 1.2, the gene encodes L-type a1C Ca 21 channel, die before day 14.5 postcoitum, and displayed a profound decrease in myocardial contractility [17]. Although it is becoming increasingly clear that Ca 21 signaling plays a fundamental role in the migration of a variety of cell types, such as neutrophils [18], eosinophils [9], neurons [19], fibroblast [20], and smooth muscle cells [21], to our knowledge no study has reported the role of VGCC regulated by IL-6 signaling in MSC trafficking.…”
Section: Introductionmentioning
confidence: 99%